PENGAMANAN CITRA GRAYSCALE MENGGUNAKAN ALGORITMA AES 128 DENGAN KUNCI CITRA GRAYSCALE - Umam, Ahmad Khoirul; Kamsyakawuni, Ahmad; Riski, Abduh (Majalah Ilmiah Matematika dan Statistika, 2018)
Cryptography is the science of maintaining or securing an information by scrambling or hiding information so that it is difficult to analyze. The algorithm used in this study is the AES 128 algorithm that has been changed using the grayscale image. The AES algorithm is a modern algorithm that replaces the DES algorithm, and is an algorithm that is chosen to secure a data / message because it is efficient and has strong security. In the process, the grayscale image key is divided into 16 blocks of pixels, pixels are operated on each block with XOR operations so that one character will be obtained for each block. From the XOR process of pixels in 16 blocks, 16 characters or 128 bits long will be obtained. The data used in this study are plain images in the form of grayscale images and keys in the form of grayscale images as well. Grayscale (plain image) images will be encrypted with an image key that is also a grayscale image. Initially, the key will be taken from a grayscale image by dividing 16 blocks to get a 128-bit long key, then generating the key with the key generator in the AES algorithm so that it will get 10 sub-keys. Then encryption is done with 10 subkeys that were obtained using the AES algorithm. The results of the encryption process will produce an encoded image or cipher image that does not contain information from the plain image. The results of this algorithm are fairly safe against attacks because they have varied and sensitive keys. Keywords: Cryptography, AES, Rijndael Algorithm, Grayscale